PENGARUH HUTANG JANGKA PENDEK, PERPUTARAN PIUTANG DAN MODAL KERJA TERHADAP PROFITABILITAS PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA - Paramita, Nurul Indah; Efriyenti, Dian (LPPM Universitas Putera Batam, 2019)
Thisi studyi entitled thei influence of short-term debt, accounts receivable turnover and working capital on profitability in manufacturing companies in the food and beverage subsector listed on the Indonesia Stock Exchange in 2013-2017. This study aims to determine short-term debt, accounts receivable turnover and working capital both partially and simultaneously. The population of this study is a food and beverage sub-sector manufacturing company listed on the Stock Exchange in 2013-2017, which was included in the period of 5 years so that 40 samples were obtained and this sample study used purposive sampling, namely sampling technique in accordance with certain criteria and obtained by 8 companies. Processing data using SPSS version 22 software. The datai analysisi methodi usedi isi multiplei lineari regressioni methodsi. Thei resultsi ofi thei t-testi analysis partially indicate thati short-term debt does not have a significant effect on profitability, receivable turnover does not significantly influence profitability , while working capital has a significant effect on profitability. The results of the F test analysis show that simultaneously or together there is a significant influence between the variables of short-term debt, accounts receivable turnover and working capital on profitability.